DIRECTIVES AND THE SWORN TRANSLATOR: THE TERMINOLOGICAL CHALLENGE OF THE MDD 93/42/EEC - KOŚCIAŁKOWSKA-OKOŃSKA, Ewa (Comparative Legilinguistics, 2016)
The presentation addresses the field of translating EU texts (directives), specifically the Medical Device Directive. The translation of EU instruments lies within the scope of responsibilities of the translators working for the European Commission and the European Parliament. Yet, sworn translators working in their native countries face the need to translate medical documentation both for natural persons (that is necessary for administrative purposes) and for corporate bodies (that operate on the common European market and require e.g., declarations of conformity, instructions for use or EC design examinations certificates to commercialise their products and thus run their business). Naturally, sworn translators while performing tasks commissioned refer to and consult the accepted translated versions of EU instruments to remain in line with the versions that have been transposed into their national legislations. In this paper, the original (English) and the translated (Polish) versions of the Medical Device Directive (93/42/EEC) shall be compared and analysed to find whether the Polish version fully reflects assumed terminological consistency.